Intracellular Inclusions Induced by Patient-Derived and Amplified α-Synuclein Aggregates Are Morphologically Indistinguishable - Rabab Al-Lahham; Mark E. Corkins; Mohd Ishtikhar; Prakruti Rabadia; Santiago Ramirez; Victor Banerjee; Mohammad Shahnawaz (Cells)
Lewy Body Disease (LBD) and Multiple System Atrophy (MSA) are synucleinopathies with distinct prognoses and neuropathologies, however, with overlapping clinical symptoms. Different disease characteristics are proposed to be determined by distinct conformations of alpha-synuclein (α-Syn) aggregates, which can self-propagate and spread between cells via a prion-like mechanism. The goal of this study is to investigate whether α-syn aggregates amplified from brain and CSF samples of LBD and MSA patients using the Seed Amplification Assay (SAA) maintain α-Syn seeding properties similar to those of α-syn aggregates derived from patients’ brains. To address this, SAA-amplified and un-amplified α-Syn aggregates from LBD and MSA patients’ brains, as well as SAA-amplified α-Syn aggregates from LBD and MSA patients’ CSF samples, were used to treat synuclein biosensor cells, and induced intracellular α-Syn inclusions were analyzed by confocal microscopy. Our data indicate that induced α-Syn aggregates from LBD and MSA patients’ brains have similar seeding properties and morphological characteristics in the α-Syn biosensor cells as those amplified from LBD and MSA patients’ brains, as well as those amplified from LBD and MSA patients’ CSF samples. In this study, we demonstrated that, regardless of the source of aggregates, the seeds from LBD and MSA produce cellular accumulation of α-Syn with distinct morphologies, confirming the presence of different conformational strains of α-Syn in LBD and MSA and allowing us to differentiate synucleinopathies based on the morphology of aggregates and seeding properties.